Host and environmental factors of malaria among Orang Rimba in Jambi: a host intermediate characteristics study - Budiyono; Kristiawan; Sutiningsih, Dwi (BKM Public Health and Community Medicine, 2021)
Purpose: This research aimed to prove and analyze the host's characteristics and perceptions, and the environment that affected the existence of the Orang Rimba tribe. Method: This research employed a mixed-methods approach, combining analytical-qualitative and quantitative research methods within a cross-sectional design. Results: The results showed that the host factor influencing malaria incidence was the productive age category with a value of Exp.B=0.062 (95% CI 0.004-0.915; p-value = 0.043). Most respondents perceived that malaria often attacked at the peak of the fruit season. To control it, respondents consumed traditional medicine, used smoke, and increased mobilization to natural forest areas. Meanwhile, the host and environmental factors that did not affect malaria incidence included the density of Anopheles larvae, Anopheles mosquitoes, and predatory animals, as well as traditional medicine habits, the use of mosquito nets, hunting practices, and respondents' residence location. Conclusion: The definitive host characteristics that influenced malaria incidence were productive age, host perception, and host behavior.